2018
DOI: 10.1111/1756-185x.13341
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations due to systemic connective tissue diseases: Secular trends and regional disparities in Sweden, 1998‐2016

Abstract: There were substantial decreases in the absolute and relative burden of SCTD hospitalizations reflecting possible improvements in disease management in Sweden. The rising trend in PANRC among the youngest children warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…However, the overall reduction from 2011 to 2019 was relatively small (À4.8%) compared with another analysis from Sweden, which also used joinpoint analysis, in which the reduction was 57% in the whole study period (1998-2013). 14 Although the direct factors of this reduction were not evaluated in our study, a possible explanation is that previous therapies may have had a beneficial impact that contributed to less hospitalizations, together with the possibility that more expert outpatient care may prevent admissions, which may prevent around 13% of avoidable hospitalizations. 15 Previous studies, in other geographic regions, mainly Europe, have also reported a decrease in hospitalization trends in the last decade.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…However, the overall reduction from 2011 to 2019 was relatively small (À4.8%) compared with another analysis from Sweden, which also used joinpoint analysis, in which the reduction was 57% in the whole study period (1998-2013). 14 Although the direct factors of this reduction were not evaluated in our study, a possible explanation is that previous therapies may have had a beneficial impact that contributed to less hospitalizations, together with the possibility that more expert outpatient care may prevent admissions, which may prevent around 13% of avoidable hospitalizations. 15 Previous studies, in other geographic regions, mainly Europe, have also reported a decrease in hospitalization trends in the last decade.…”
Section: Discussionmentioning
confidence: 83%
“…This aspect may have an impact on the slight reduction of hospitalizations compared to a more significant decrease in other countries. 14 Interestingly, in males with SLE, the hospitalization rates were stable over the period analyzed; however, the number of cases in this gender group was relatively small. A large sample size might show a different trend modification that must be shown in future research since men with SLE are at higher risk for some lupus morbidities, like renal and cardiovascular.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The disorder, however, has a marked predilection for women and similar to SLE, the female:male ratio is approximately 9:1. The disease usually presents in middle age but may occur in children as well as the elderly (5,6).…”
Section: Introductionmentioning
confidence: 99%